(3aVGFM GdHGWfjI haVGFd GdeSJXgQjIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3CHh GdMSf Ydi Hf SYjO Hf eSYhO s)
(3ChdgG (B:s
(3GdMeO ddg GdMi Gdbjhe CeG HYO hCHOjJ dJUfja gPG GdcJGH eYfjG Ydi YTQI CHhGH hSejJg aVGjM GdHGWfjI s
(3BNQgG (B:s
(3hbO Qhi Yf YHO Gddg Hf eSYhO Cf QShd Gddg Udi Gddg Ydjg hSde bSe bSekG abGd QLd ef GdCfUGQ gPg bSeI eG CQjO HgG hLg Gddg JYGdi fLR HMeO Gddg hbhJg s
(3QJHg Ydi YTQI CHhGHs
(3eWehSI GdYfhGfs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
Keywords: (3GdJhMjO hGdedd hGdfMds